PENGARUH MEDIA PUZZLE TERHADAP KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIDIK KELAS I SEKOLAH DASAR - Addawiyah, Nazil Bahri; Wati, Tri Linggo (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to introduce and implement puzzle-based learning media to improve first-grade students’ early reading skills in elementary school. The research employed a quantitative approach using a pre-experimental method with a one-group pretest–posttest design. The participants were 30 first-grade students at SDN Ganggang Panjang Tanggulangin Sidoarjo, selected using a saturated sampling technique. Data were collected through pretest and posttest instruments based on five indicators of early reading skills proposed by Farida Rahim: letter recognition, word reading, sound–letter correspondence, reading fluency, and reading comprehension. Data analysis was conducted using normality testing (Shapiro–Wilk) and paired samples t-test with the assistance of IBM SPSS Statistics. The results showed a significant difference between pretest and posttest scores, with a significance value of 0.000 (p < 0.05). These findings indicate that puzzle media has a significant effect on improving students’ early reading skills. In conclusion, puzzle-based learning media can serve as an effective and engaging instructional strategy to enhance early reading skills in lower-grade elementary students.